2015
DOI: 10.1007/s10433-015-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

How voluntary is the active ageing life? A life-course study on the determinants of extending careers

Abstract: In Switzerland, as in many other European states, there is an increasing emphasis in public policy on promoting later retirement from the labour market. But this accelerating drive in Swiss policy-making to extend occupational activity does not mean that every worker is currently likely to retire late, nor does it imply that all those who do retire late do so voluntarily. This article uses a life-course approach, first to study the determinants of late retirement, and secondly to analyse whether the decision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Being not married or cohabiting and having a higher income were found to positively associate with late retirement. This is in line with previous research that have found that that married or cohabiting individuals tend to retire earlier [ 50 ]. Interestingly, sex did not differ between retirees in the regression analyses.…”
Section: Discussionsupporting
confidence: 93%
“…Being not married or cohabiting and having a higher income were found to positively associate with late retirement. This is in line with previous research that have found that that married or cohabiting individuals tend to retire earlier [ 50 ]. Interestingly, sex did not differ between retirees in the regression analyses.…”
Section: Discussionsupporting
confidence: 93%
“…In the developed world, strategies have been implemented to promote economic activities among aged workers, including incentives for late retirement, penalties for early retirement and an increase in or abolishment of the age of mandatory retirement. 3 Older retirement age means that more employees beyond the age of 55 years will remain in the workforce. 4 While a number of mental and social abilities can improve with increasing age, and such changes should be viewed as strengths and be respected, 4 age-related physiological decline requires special considerations Strengths and limitations of this study ► This systematic review was registered in PROSPERO.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, and importantly, it is often difficult to determine whether retirement timing is the choice of the individual or whether it is imposed by employers or legal requirements relating to pension rights. As Scherger (2015) and Madero-Cabib and Kaeser (2016) have pointed out, an individual who works past a given legal retirement age may not do so ‘voluntarily’ but out of necessity to acquire more income or to avoid the application of a regressive calculation of their pension income due to missing insurance contributions (Aubert et al , 2013).…”
Section: Methodsmentioning
confidence: 99%